1982
DOI: 10.1073/pnas.79.23.7273
|View full text |Cite
|
Sign up to set email alerts
|

Restriction of motion of protein side chains during the photocycle of bacteriorhodopsin.

Abstract: Linear dichroism was measured during the photocycle of bacteriorhodopsin. The anisotropy of the sample was produced by the photoselection method. The measurements on purple membrane fragments embedded in agar gel were performed at room temperature with 200-psec time resolution at several wavelengths in the 240-to 550-nm spectral region. The induced anisotropy of the retinal chromophore remained constant after the formation of the photocycle intermediate M. The anisotropy was also time independent at the charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The observation of reorientational motion triggered by light absorption and consequently correlated with the BR photocycle suggests that these reorientational motions might play a functional role in the proton-pumping mechanism of the purple membrane. These motions, however, are not essential to the proton-pumping mechanism, since monomeric BR and BR immobilized in gels are still capable of pumping protons (21,22). If the reversible rotational model with reorientation of spectator BR monomers is correct, the role of these reorientations may well be related to the puzzling question:…”
Section: Functional Role Of Rotationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The observation of reorientational motion triggered by light absorption and consequently correlated with the BR photocycle suggests that these reorientational motions might play a functional role in the proton-pumping mechanism of the purple membrane. These motions, however, are not essential to the proton-pumping mechanism, since monomeric BR and BR immobilized in gels are still capable of pumping protons (21,22). If the reversible rotational model with reorientation of spectator BR monomers is correct, the role of these reorientations may well be related to the puzzling question:…”
Section: Functional Role Of Rotationsmentioning
confidence: 99%
“…Orientational motion in the PM has also been investigated, principally by linear dichroism spectroscopy, which detects reorientation of the retinal chromophore following polarization-selective excitation of BR (18)(19)(20)(21)(22)(23). Some of these studies have detected reorientation in BR during the M--N-*O->BR transition (18,19,22,23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But none of the devices studied to date tests the ultimate capability of the protein to provide an ultrafast response. To establish the full potential of such integrated devices and circuits for high speed applications, it is necessary to characterize the dynamics of the initial (B1) photovoltage transient (Blaurock and Stoeckenius, 1971;Khorana et al, 1979;Czege et al, 1982;Kononenko et al, 1987;Henderson et al, 1990). This study determines the initial (fast) photovoltaic response of the protein by using a technique with an effective 3-dBbandwidth of 350 GHz, a temporal resolution roughly six times greater than previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…If repeated determinations find that there is a small but significant increase in the slowest time constant for membranes encased in gel, a likely explanation is that the recovery of BR from M entails the greatest conformational change of the bR or membrane, as indicated by the anisotropy values of Song et al 6 and the high viscosity of the gel impedes this transition. The idea that there is significant rotational diffusion of PM in suspensions that can lead to distortions of kinetic data emanating from reorientations of the retinal chromophore in photoselected populations seemed to be supported by Czege et al 8 who reported that embedding PM in agar gels removed the changes in anisotropy observed in suspensions. They concluded "the direction of the retinal chromophore (and consequently of the retinal itself) does not change even during the transitions of the photocycle."…”
mentioning
confidence: 94%